Strategi Kepala Sekolah dalam peningkatan kedisiplinan peserta didik di SMP Negeri 2 Plandaan Jombang - Silvia Rismawati; Ashari Ashari (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
This research is a qualitative research and the subject of this research is the principal and students. Data are obtained through observation, interviews and documentation. Data analysis was carried out using qualitative analysis. The results showed that (1) The principal's strategy in disciplining students in state junior high schools 2 Plandaan, carried out by planning in creating empathic behavior, organizing by prioritizing good communication, implementing learning discipline activities; coaching and supervision of teacher performance, providing motivation, awarding and evaluating learning discipline activities. (2) obstacles in the principal's strategy in disciplining students at SMP Negeri 2 Plandaan are accompanied by the lack of parental attention and the lack of awareness of students accepted by students, Different student backgrounds. Communicating with Parents of Learners, Educational Media and educational environment. Keywords: principal strategy, discipline.